A meta-analysis comparing intramedullary with extramedullary fixations for unstable femoral intertrochanteric fractures. Issue 37 (September 2019) - Sun, Dawei; Wang, Chunling; Chen, Yuhui; Liu, Xiaochun; Zhao, Peng; Zhang, Hongan; Zhou, Hui; Qin, Chenghe
Abstract: Purpose: To find out whether the intramedullary fixations are superior to the extramedullary fixations in treating unstable femoral intertrochanteric fractures (UFIFs). Methods: The meta-analysis of randomized controlled trials (RCTs) was conducted by searching the PubMed, Cochrane Library, and Embase databases to evaluate functional scores, surgical outcomes, and adverse events in adult patients receiving intramedullary fixations in comparison to extramedullary fixations. Risk ratio (RR) or weighted mean difference (WMD)/standard mean difference (SMD) with 95% confidence intervals (CIs) were calculated as effect sizes. Results: A total of 18 RCTs, comprising 2414 patients, were included in this meta-analysis. Primary efficacy outcome: Parker scores [weighted mean difference, 1.10, 95% confidence interval (CI), 0.64–1.55; P < .0001] and Harris hip scores [risk ratio, 1.24, 95%CI, 1.09 –1.41; P = .0008] were higher in the intramedullary fixation group. Moreover, blood loss, operative time, length of incision, hospital stay, and implant failure were superior in the intramedullary fixation group. Other secondary efficacy outcome: No significant differences were found between the 2 groups in terms of fluoroscopy time, mortality, cut-out, nonunion, superficial wound infection, later fracture, and reoperation. Conclusions: This meta-analysis suggested that intramedullary fixation is more effective and safer than extramedullary fixation in treating UFIFs. Furthermore, blood loss, operative time, length of incision, hospital stay, and implant failure were superior in the intramedullary fixation group. Abstract : Supplemental Digital Content is available in the text